GENDER DISCRIMINATION REFLECTED IN THEIR EYES WERE WATCHING GOD BY ZORA NEALE HURSTON: FEMINIST APPROACH - Agus Triyogo; Chairunnisa Chairunnisa (JELLT (Journal of English Language and Language Teaching), 2017)
This study aims to analyze gender discrimination reflected in novel Their Eyes Were Watching God by Zora Neale Hurston. This study reveals kinds of gender discrimination as reflected in the novel and how the gender discrimination affects characters as reflected in the novel. This study employed feminist approach. The writers only focused on analyzing gender discrimination issue limited on woman. The results show that the kinds of gender discrimination found in the novel were natality inequality, mortality inequality, household inequality, special opportunity inequality, and professional inequality. The effect of gender discrimination covered physical problems, psychological problems, impact on women’s family and dependent, and impact on social.